Gene-related Parkinson's disease diagnosis via feature-based multi-branch octave convolution network. (September 2022) - Lei, Haijun; Zhang, Yuchen; Li, Hancong; Huang, Zhongwei; Liu, Chien-Hung; Zhou, Feng; Tan, Ee-Leng; Xiao, Xiaohua; Lei, Yi; Hu, Huoyou; Huang, Yaohui; Lei, Baiying
Abstract: Parkinson's disease (PD) is a common neurodegenerative disease in the elderly population. PD is irreversible and its diagnosis mainly relies on clinical symptoms. Hence, its effective diagnosis is vital. PD has the related gene mutation called gene-related PD, which can be diagnosed not only in the specific PD patients, but also in the healthiest people without clinical symptoms of PD. Since mutations in PD-related genes can affect healthy people, and unaffected PD-related gene carriers can develop into PD patients, it is very necessary to distinguish gene-related PD diseases. The magnetic resonance imaging (MRI) has a lot of information about brain tissue, which can distinguish gene-related PD diseases. However, the limited amount of the gene-related cohort in PD is a challenge for further diagnosis. Therefore, we develop a joint learning framework called feature-based multi-branch octave convolution network (FMOCNN), which uses MRI data for gene-related cohort PD diagnosis. FMOCNN performs sample-feature selection to learn discriminative samples and features and contains a deep neural network to obtain high-level feature representation from various feature types. Specifically, we first train a cardinality constrained sample-feature selection (CCSFS) model to select informative samples and features. We then establish a multi-branch octave convolution neural network (MBOCNN) to jointly train multiple feature inputs. High/low-frequency learning in MBOCNN is exploited to reduce redundant feature information and enhance the feature expression ability. Our method is validated on the publicly available Parkinson's Progression Markers Initiative (PPMI) dataset. Experiments demonstrate that our method achieves promising classification performance and outperforms similar algorithms. Graphical abstract: Image 1 Highlights: A joint learning framework called feature-based multi-branch octave convolution network (FMOCNN) for gene-related cohort PD diagnosis. The cardinality-constrained sample feature selection (CCSFS) model selects informative samples and features. A multi-branch octave convolution neural network (MBOCNN) is established to reduce redundant feature and enhance the feature expression ability.